Finite-element analysis of strains in seepage barriers of the earth dam. Issue 3 (12th July 2019) - Athani, Shivakumar S.; Solanki, Chandresh H.; Dodagoudar, Goudappa R.; Shukla, Sanjay K.
Abstract : This paper presents the strain profiles obtained along the height of the seepage barriers of the earth dam. The seepage barriers are employed in the permeable dam section in order to obstruct the seepage of water from upstream to downstream and thereby reducing the risk of piping. A total of 36 finite-element simulations were carried out in the study, wherein the combination and placement of the cut-off walls in the earth dam section were varied. The results include the horizontal, vertical and shear strain profiles and their variation along the height of barriers with respect to its position for different reservoir conditions, such as high reservoir and 5 d drawdown conditions. By the adoption of single barrier in the dam section, the strain values were found to be on the higher side when compared with the near-end barrier in double-configuration system under high reservoir conditions, whereas for the drawdown conditions, the magnitude of the strains in the barrier were more or less the same. The higher strain levels induced in the barrier could cause cracking of the barrier, thereby impairing the function of the barrier.